ANALISIS PENERIMAAN RETRIBUSI PARKIR TEPI JALAN UMUM DI KOTA JAYAPURA - Stephanny Inagama Timisela; Meinarni Asnawi; Yundy Hafizrianda (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2017)
The purpose of this research was to acquire the information about magnitude of potential and level of leakage to income of parking retribution in road side in Jayapura municipality. A sampling tehnique in this research was Slovin technique and data collection techniques were observation, interview and literature review. There were 2 data analysing approach employed such as quantitative and qualitative approach. The quantitative technique was to measure growth, contribution, elasticity, and calculation of potential and level of leakage. Meanwhile, the qualitative technique was for the description analysis based on research findings. The findings of this research showed that: (a) management of parking retribution in road side in Jayapura municipality was not yet effective to optimise the potentialities of own source local revenue; (b) the research findings revealed that the perking retribution for Road Side in Jayapura municipality was IDR 914.928.000,- per year with 59.13 per cent level of leakage or equal to IDR 373.968.000,- per year; (c) there were some strategies to anticipate the issue of leakage in realisation and potential optimisation of road side parking in Jayapura municipality such as improvement and managing regulation, human resource, the society awareness, institutional system and procedures. Keywords: Own Source Local Revenue, Retribution of Road Side parking, Leakage